Political distrust, perceived threat, and intentions to engage in normative and violent collective action: A mixed‐methods study - Gulliver, Robyn; Chan, Christian S.; Tam, Katy Y. Y.; Lau, Iris S. K.; Hong, Ying Yi; Louis, Winnifred R. (European journal of social psychology, 2023)
In three studies, we examined the role of distrust and perceived threat in intentions to engage in normative and violent non‐normative collective action. A field‐based qualitative study of 35 pro‐democracy protestors during the 2019 Hong Kong Anti‐Extradition protests revealed that perceived threat to Hong Kong values alongside distrust of political institutions spurred collective action engagement and support for defensive violent collection action. In Study 2, a questionnaire (N = 639) testing pro‐democracy action intentions demonstrated direct paths on both normative and violent collective action intentions from distrust and threat. In Study 3 (N = 133), experimental trust and threat manipulations demonstrated a significant association between distrust and threat on violent collective action intentions and acceptance, and a significant interaction on acceptance of violent collective action. Our results reveal the importance of distrust and threat in attitudinal support for, and engagement in, collective action and their role in transitioning from non‐violent to violent collective action.